PENGARUH METODE GLASS ANALYSIS TERHADAP SELF-EFFICACY MEMBACA DAN READING LEVEL (STUDI PADA SALAH SATU SISWA KELAS 3 SD DENGAN KESULITAN MEMBACA DI SEKOLAH INKLUSI DI TANGERANG SELATAN) - Khasanah, Nurul (Esa Unggul University, 2020)
This study aims to examine the effect of the glass analysis method on reading self-efficacy and reading levels in grade 3 elementary school students who have difficulty in reading. Glass analysis is one method of reading for students who experience reading difficulties, focuses on decoding. Glass analysis intervention was investigated to prove its effect on self-efficacy reading and reading levels. Self-efficacy is a person's belief in his ability to master tasks. The results of the effort are reading level, which is a proof of the success of the effort that has been achieved by students in reading skills. Determination of the sample using non probability sampling with purposive sampling technique. The subject consists of two, one experimental subject and one comparison subject. The experimental subjects received glass analysis intervention, while the comparison subjects described the reading and reading self-efficacy level of grade 3 elementary school students. The research variables were measured using two instruments, The Reader Self-Perception Scale (33 items) and informal reading tests. The data of the study were analyzed using paired-sample t test, so that the results obtained that glass analysis has not been able to influence reading self-efficacy (z = -1.0 and p> 0.05) and reading level (z = -1.0 and p> 0 ,05).Keyword: Glass Analysis, Self-Efficacy Membaca, Reading Level